EKSPLORASI BILANGAN TERHUBUNG PELANGI LOKASI PADA GRAF ULAR SEGITIGA - Bustan, Ariestha Widyastuty; Hi Dahlan, Akmal; Kharie, Diyah Safitri Qammariyah (Universitas Pasifik Morotai, 2025)
The concept of the locating rainbow connection number in a graph is an innovation in graph coloring theory that combines the ideas of rainbow vertex coloring and partition dimension in graphs. This concept aims to determine the smallest positive integer such that there exists a locating rainbow -coloring of the graph, allowing each vertex to have a unique rainbow code. In this study, we investigate the locating rainbow connection number of the triangle snake graph. The method employed involves analyzing the graph’s structure and constructing rainbow vertex-paths that ensure the uniqueness of the rainbow code for each vertex. The results show that, for graphs of order greater than five, the locating rainbow vertex-connection number of a triangle snake graph is equal to the number of cut-vertices in the graph